2013
DOI: 10.1109/tnano.2012.2226188
|View full text |Cite
|
Sign up to set email alerts
|

Non-Surface-Treated Au/ZnO Schottky Diodes Using Pre-Annealed Hydrothermal or Sol-Gel Seed Layer

Abstract: Nonsurface-treated zinc oxide (ZnO) Schottky diodes were fabricated on a Si substrate using one of two different seed layers, prepared by either the sol-gel or hydrothermal method. Then, ZnO film was grown on a seed layer by the hydrothermal method, and Au/ZnO Schottky diodes were fabricated to study the effects of different seed layers on the electric behavior. Observations show that the Schottky diodes grown on a hydrothermal seed layer exhibit very good rectifying behavior with a rectification ratio as larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The linear I∼V relation, for V < 0.15 for all the three Pd/ZnO Schottky diodes shows ohmic behavior of the device commonly attributed to the tunneling of charge carriers between the states at the interfaces [5]. For V > 0.15 V, the diodes nearly follow I ∼ exp (V) relation possibly due to the recombination tunneling mechanism [5].…”
Section: Results and Disscussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The linear I∼V relation, for V < 0.15 for all the three Pd/ZnO Schottky diodes shows ohmic behavior of the device commonly attributed to the tunneling of charge carriers between the states at the interfaces [5]. For V > 0.15 V, the diodes nearly follow I ∼ exp (V) relation possibly due to the recombination tunneling mechanism [5].…”
Section: Results and Disscussionmentioning
confidence: 81%
“…The major difficulty in achieving a good SC on ZnO thin films is associated with the large density of intrinsic defects (especially oxygen vacancies) on the ZnO film's surface which may provide a leakage path to the device current thereby degrading the rectifier behaviour of ZnO Schottky diodes [4]. The effect of surface defects on the ZnO film's surface can be eliminated by using a very thin seed layer of a suitable material including ZnO [5], [6], Zn [7], Al 2 O 3 [8] on the surface of substrates on which ZnO films are required to be grown. The seed layers can reduce the lattice mismatching between the substrates and ZnO material thereby improving the structural, optical, and electrical characteristics of the ZnO films.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few reports present in the literature on ZnO Schottky diode using buffer layers. Hwang et al [20] reported the Au/ZnO Schottky diode using pre-annealed seed layer. The seed layer was deposited by two methods.…”
mentioning
confidence: 99%